Komparasi Sistem Pendidikan Indonesia dengan Negara-Negara OECD - Sumiyaty , Sarry; Silvia Dwi Prastiwi; Sisi Yuliana; Wahyuning Tri Mardiyanti (Journal of Contemporary Issue in Elementary Education, 2023)
The purpose of writing this article is to study a comparative study of the education system in Indonesia with OECD countries such as Japan, Singapore, Finland and the Netherlands. The background for writing this article is the success of implementing the education system in OECD countries compared to the education system in Indonesia, where there are still many gaps. Because the OECD countries mentioned are countries that are known worldwide for their success in the field of education systems. The writing carried out by this author is research in the form of diagnostics. The writing method used is the literature review method. The results of the study show that the policies taken by the Indonesian government in the education system are not much different from OECD countries. However, the difference lies in the implementation in the field. There are still many gaps due to several factors, including geographical and human factors. These factors are what hinder development in the world of education in Indonesia.